1997
DOI: 10.1136/adc.77.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of zinc supplementation in malnourished Bangladeshi children with acute diarrhoea

Abstract: Objective-To evaluate the impact of zinc supplementation on the clinical course, stool weight, duration of diarrhoea, changes in serum zinc, and body weight gain of children with acute diarrhoea. Design-Randomised double blind controlled trial. Children were assigned to receive zinc (20 mg elemental zinc per day) containing multivitamins or control group (zinc-free multivitamins) daily in three divided doses for two weeks. Setting-A diarrhoeal disease hospital in Dhaka, Bangladesh. Patients-111 children, 3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
2
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 24 publications
2
81
2
2
Order By: Relevance
“…The findings indicate that zinc supplementation resulted in faster recovery from diarrhoea; the 50% shorter median duration of illness as observed in this study is greater than that has been observed in our earlier studies in young children with acute watery diarrhoea, (Roy et al, 1997) and persistent diarrhoea (Roy et al, 1998;The Zinc Investigators' Collaborative Group, 2000) and cholera (Roy et al, 2006a).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The findings indicate that zinc supplementation resulted in faster recovery from diarrhoea; the 50% shorter median duration of illness as observed in this study is greater than that has been observed in our earlier studies in young children with acute watery diarrhoea, (Roy et al, 1997) and persistent diarrhoea (Roy et al, 1998;The Zinc Investigators' Collaborative Group, 2000) and cholera (Roy et al, 2006a).…”
Section: Discussioncontrasting
confidence: 38%
“…An earlier Bangladeshi study had also observed significant increase in the mean body weight of children with acute diarrhoea who received zinc (Roy et al, 1997). Another Jamaican study observed increase in the lean tissue mass of children during their nutritional rehabilitation (Golden and Golden, 1981).…”
Section: Table 1cmentioning
confidence: 94%
“…Study characteristics are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Only three studies had a population of fewer than 100 patients, and all studies were conducted in countries considered to be "emerging and developing economies" (48).…”
Section: Resultsmentioning
confidence: 99%
“…This element stabilizes the cell membrane, and zinc deficiency disrupts the intestinal mucosa, reduces brush border enzymes and increases mucosal permeability and the intestinal secretion of water. 17,18 Zinc also acts as a potassium channel blocker, inhibiting cyclic adenosine monophosphate-mediated chlorine secretion. 19 Zinc supplementation during diarrhoea can therefore reduce the severity and duration of the episode.…”
Section: Introductionmentioning
confidence: 99%